2023
DOI: 10.1080/10872981.2023.2217549
|View full text |Cite
|
Sign up to set email alerts
|

From self-regulation to co-regulation: refining learning presence in a community of inquiry in interprofessional education

Abstract: Introduction Online interprofessional education is a collaborative process that emphasizes both individual reflection and shared discourses. A useful analytical tool for understanding the complex dynamics of online collaborative learning is the community of inquiry (CoI) framework, which originally held that there are three types of presence in such learning: teaching, cognitive, and social. However, it was later revised to include learning presence, which is characterized by self-regulated learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
(60 reference statements)
2
5
0
Order By: Relevance
“…The results showed that students perceive all three CoI presences as necessary in the online learning setting. The results are supported by the findings of Akyol and Garrison (2008), Mutezo and Mar e (2022), Shea and Bidjerano (2010) and Zheng et al (2023), who also found significant associations between the three presences. Huang and Lee's (2022) study echoed this study's findings with the most significant coefficient between TP and CP.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results showed that students perceive all three CoI presences as necessary in the online learning setting. The results are supported by the findings of Akyol and Garrison (2008), Mutezo and Mar e (2022), Shea and Bidjerano (2010) and Zheng et al (2023), who also found significant associations between the three presences. Huang and Lee's (2022) study echoed this study's findings with the most significant coefficient between TP and CP.…”
Section: Discussionsupporting
confidence: 78%
“…Their study also showed that students with higher perceived SP had a tendency towards higher shared metacognition. A recent study by Zheng et al (2023) found that students' SR is shaped by their social interactions and regulation with others. The findings indicated that a student's CR can significantly predict SR in an online collaborative setting.…”
Section: Relationship Between the Shared Metacognition And Community ...mentioning
confidence: 99%
“…[20][21][22] Self-evaluation, on the other hand, has been examined in medical education, [23][24][25][26] but fewer investigations were noted in interprofessional education. 27,28 In Reinders and Krijnen's 3 study, they examined how interprofessional identity influences outcomes such as group effort and interprofessional direction. Although they established promising results on the interprofessional identity in IPE that can influence the said outcomes, further examination of other related variables can benefit the literature and practice of IPE.…”
mentioning
confidence: 99%
“…Self-evaluation, on the other hand, has been examined in medical education, [23][24][25][26] but fewer investigations were noted in interprofessional education. 27,28 In Reinders and Krijnen's 3 study, they examined how interprofessional identity influences outcomes such as group.…”
mentioning
confidence: 99%
See 1 more Smart Citation